Environmental control of development - Bertero, Hector Daniel (2015)
The duration of development stages is one of the keydetermining factors of the adaptation of a species,conditioning adjustment to the growing season, thedistribution of photoassimilates, water and nutrientabsorption and lastly, the yield achieved. Four factorsaffect the progression of quinoa development: temperature,photoperiod, hydric status and radiation;the last two variables have been barely analysedin terms of its impact on development and there isdocumented genetic variability regarding sensitivityfor the first two. Temperature is the environmentalfactor with the highest relative impact on durationof development. Sensitivity to temperature wasevaluated for the time to visible floral buds and leafappearance rate; variability for both variables is associatedwith characteristics of the original environments,being higher in environments with limitedwater and low temperatures, indicating that adaptationto short growing seasons is expressed throughhigher earlyness, partly offset by a higher leaf appearancerate, whilst most late genotypes are foundin more humid and warmer environments. Quinoabehaves as a short-day plant and the higher photoperiodsensitivity is expressed in valley genotypes,grown between Argentina and Colombia. At the oppositeextreme, those in the southern Altiplano, includingBolivia and north-western Argentina, togetherwith Chilean sea-level genotypes, show little or nosensitivity to this factor in respect of time to flowering.Photoperiod sensitivity is manifested from theearly stages of development up to advanced stagesof grain filling; there is also variability in the duration of the sensitive period.